Perception of the risk of arrest for drinking and driving - Wieczorek, William F. (Criminal justice and behavior, 1994)
This study examined the relationships among drinking measures, drinking and driving variables, and the perception of the risk of being arrested for driving while impaired by alcohol (DWI). Random-digit dialing procedures were used in association with computer-assisted telephone interviewing to collect data from 453 drivers aged 18 and older who drank alcoholic beverages in the last 12 months. Subjects were categorized by their perceptions of the risk for DWI arrest into a high probability of arrest group (at least 1 in 10 chance for arrest) and a low probability group (a 1 in 100 chance or less). Men in the high probability of arrest group were significantly heavier drinkers than those in the low probability group. Women who drank heavily in a single sitting also tended to express a higher perceived risk of DWI arrest. Age differences in DWI arrest probability also were uncovered. These results suggest that DWI prevention efforts need to be directed at specific groups and that for some groups, such as heavier drinkers, efforts other than deterrence are needed